Behavior of Investors VS Traders in Determining Share Prices with Intrinsic Value Moderation (Evidence of Random Walk Hypothesis) in the Indonesian Pandemic Time 2019-2021 - Indahwati Indahwati; Ni Ketut Yulia Agustini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The pandemic period that started in 2019 has caused many businesses to collapse, the JCI is at the level of 6,244 (24 Jan). This resulted in the closing of the capital market on March 13, 2020 after the WHO announcement that the COVID-19 outbreak was a pandemic. Nevertheless (Rizal, 2021; 1) the reality shows that the Indonesian capital market is still growing with the increase in the number of investors, especially retail investors. This study aims to determine the behavior of market participants, namely investors and traders through stock prices. The population used in this study were 18 companies whose shares were actively traded in 2019 and 2020 and semester 1 2021, the sample was taken from companies whose shares received top gainers. The analytical model used is MRA or moderated regression analysis. The results of the study show that the capital market's revival during the pandemic is caused by the motivation of traders to obtain short-term results, namely capital gains, by using the stock's intrinsic value benchmark, without conducting in-depth technical analysis. This shows that stock prices will move randomly following past patterns which have not been proven in the pandemic conditions in Indonesia.